Association of serum uromodulin with adipokines in dependence of type 2 diabetes. (February 2022) - Then, Cornelia; Herder, Christian; Thorand, Barbara; Sujana, Chaterina; Heier, Margit; Meisinger, Christa; Peters, Annette; Koenig, Wolfgang; Rathmann, Wolfgang; Roden, Michael; Stumvoll, Michael; Maalmi, Haifa; et al.
Abstract: Background: The renal tubular glycoprotein uromodulin is associated with obesity and type 2 diabetes, but the underlying mechanisms are elusive. We investigated the association of serum uromodulin with adipokines and tested the effect modification by diabetes status. Methods: The associations of serum uromodulin with eight adipokines were assessed in 795–1080 participants of the KORA F4 study aged 62–81 years using linear regression models adjusted for sex, age, BMI, estimated glomerular filtration rate and diabetes. Significant associations were assessed for effect modification by diabetes status. We further tested using logistic regression whether adjustment for the significant adipokines affected the association of uromodulin with type 2 diabetes. Results: Serum uromodulin was inversely associated with chemerin and retinol-binding protein-4 after multivariable adjustment (p < 0.001) and Bonferroni correction for multiple testing. No significant association was observed between uromodulin and the other adipokines (leptin, adiponectin, secreted frizzled-related protein 5, progranulin, omentin-1 and vaspin) after correcting for multiple testing. The association of uromodulin with chemerin and retinol-binding protein-4 was stronger in participants with type 2 diabetes than in participants without diabetes (p for interaction < 0.05). However, inclusion of chemerin and retinol-binding protein-4 in logistic regression models did not attenuate the association of serum uromodulin with diabetes. Conclusions: Serum uromodulin was inversely associated with the predominantly pro-inflammatory adipokines chemerin and retinol-binding protein-4. The associations were stronger in participants with type 2 diabetes compared to participants without diabetes. However, the association of serum uromodulin with type 2 diabetes was independent of chemerin and retinol-binding protein-4.